The study of the processes of managing superficial properties of the solid phase of dispersed systems "clay raw materials - corrective additive" - Beisekeyeva , Сайран; Sysembina , Карина (Рroblems of engineering and professional education, 2023)
Under the conditions of economic reform in the market of building materials conducted in the Republic of Kazakhstan and the CIS countries special attention has paid to the competitiveness of finished products, in particular, products for the building facades.In turn, competitiveness determined by quality of ceramic products, their low cost and wide nomenclature that sufficiently satisfies consumer demand.In these circumstances, the application of little use raw materials and local production of wasteby optimizing formulations and targeted regulation of processes at the manufacturing stage to the final result acquires special urgency.